Productive engagement across the life course: paid work and beyond. Issue 1 (March 2013) - Loh, Vanessa; Kendig, Hal
Abstract : An uncertain economic outlook and the certitude of an ageing population highlight the importance of productive activity across all age groups for Australia's future. This paper reviews Australian and international research on productive ageing, which has typically focused on older age groups and specific activities, and presents national findings from Wave 10 (2010) of the Household, Income and Labour Dynamics in Australia (HILDA) Survey on productive activities across the life course. Both paid, tax‐generating and unpaid, voluntary activities are examined, including paid work, volunteering, caregiving, childcare, and domestic work. The kinds of productive activity people engaged in varied across age groups for men and women, highlighting the potential competition between paid work and other activities, and the importance of health and education for engagement across all ages. While the Government has begun leading actions to enhance and recognise these contributions that bring economic and social benefits both to the individual and the broader community, our research reinforces the value of investment in human capital for productive engagement across the lifespan inclusive of early, middle and later life.